Development of a Web-Based Sales Information System for Pilox Paint - Imron, Afrizal; Hidayat, Ahmad Tri (Kirana Publisher (KNPub), 2025)
In retail, efficient sales information systems improve transaction accuracy and operational productivity (Rahman, 2022). This study develops a web-based sales information system for Pilox Paint Store to streamline sales, inventory, and reporting. The goal is to address manual record-keeping, slow transactions, and stock discrepancies by digitizing operations. The system uses the Waterfall methodology: requirements, design, implementation, testing, and deployment (Li et al., 2023). Technologies include Laravel (backend), MySQL (database), and modern web frameworks to ensure scalability and security (Kumar & Singh, 2021). Testing shows 65% faster transaction processing, real-time inventory updates, and automated sales reports. User acceptance testing with store staff indicates high satisfaction (4.3/5) for usability and efficiency (Patel, 2023). The system improves data accuracy and supports management decisions. Results confirm that digitizing retail operations reduces errors and improves customer service (Anderson et al., 2022). This work demonstrates the value of web-based systems in small to medium retail and provides a reusable approach for similar stores. Future work will explore mobile integration and advanced analytics.